Talqin Method: Quality Improving of Reading the Qur'an - Tabroni, Imam (International Journal of Curriculum Development, Teaching and Learning Innovation, 2023)
In improving the quality of reading the Qur`an for female students at the Assalam Purwakarta Islamic boarding school, an appropriate method is needed to make it easier for students to be able to read the Qur`an properly and correctly according to its provisions. One method of improving the quality of reading the Qur`an is the Talqin method. This study used a quantitative experimental research approach by taking a group sample that was only given a questionnaire without comparison to other groups. The data were taken from the results of a questionnaire given to 40 female students of Assalam Purwakarta, with the final conclusion that the talqin method was able to improve the quality of reading the Qur`an for female students at the Assalam Purwakarta Islamic boarding school.